Estudo proteômico de sementes em desenvolvimento e maduras de pinhão manso (Jatropha curcas L.) - Jucá, Thiago Lustosa (2010)
Although the potential of the seed Jatropha as a source of raw material for the production of biodiesel is widely recognized, little is known about the deposition patterns of oil and protein during seed development. The availability of this knowledge will be crucial for the creation of new genotypes to meet the demand from the biodiesel industry. In this study, we performed an initial proteomic analysis of the endosperm in developing and mature in order to identify proteins involved in fatty acid metabolism as well as proteins with allergenic properties / toxic / antinutritional that are responsible for marking the residue of oil extraction unsuitable for consumption animal. Through two-dimensional electrophoresis (2DE) were established reference maps of protein fractions from the endosperm of the seed development (ESD) and mature (ESM), which were obtained by exploring the properties of differential solubility of proteins in the endosperm. These reference maps, 1480 spots in total were selected (712 "ESD" and 768 "ESM"), removed from the 2DE gel and digested with trypsin for subsequent analysis by mass spectrometry. Were used for searching the databases NCBInr and a local database of ESTs from developing seeds and during germination of Jatropha. A total of 525 spots were identified and classified functionally. Although most of the proteins identified were related reservation function, proteins involved in biosynthetic pathways of fatty acids were identified and diterpenes, as well as various metabolic-related proteins, protease inhibitors and curcina toxic protein. The relatively low rate of identification obtained in this study may in part be attributed to the fact that there is extensive databases for this species. The results presented here represent the first in-depth analysis of the deposition pattern and identification of proteins from seeds of Jatropha and lay the foundations on which the complete proteome of seeds of Jatropha can be established.